Monitoring Bacterial Conjugation by Optical Microscopy - Carranza, Gerardo; Menguiano, Tamara; Valenzuela-Gómez, Fernando; García-Cazorla, Yolanda; Cabezón, Elena; Arechaga, Ignacio (Frontiers in Microbiology, 2021)
Bacterial conjugation is the main mechanism for horizontal gene transfer, conferring 21 plasticity to the genome repertoire. Unfortunately, this process is also the major 22 instrument for the dissemination of antibiotic resistance genes. Hence, gathering 23 primary information of the mechanism underlying this genetic transaction is of a capital 24 interest. By using fluorescent protein fusions to the ATPases that power conjugation, we 25 have been able to track the localization of these proteins in the presence and absence of 26 recipient cells. Moreover, we have found that more than one copy of the conjugative 27 plasmid is transferred during mating. Altogether, these findings provide new insights 28 into the mechanism of such an important gene transfer device.